Penyerapan Tenaga Kerja Di Provinsi Jawa Timur - Fivien Muslihatinningsih; miftahul walid; I Wayan Subagiarta (UPT Penerbitan Universitas Jember, 2020)
One of the factors that can create a successful economic development in each country is the absorption of labor. The high absorption of labor will reduce poverty and increase economic growth. Thus, the government of each country is no exception, Indonesia is also carrying out reforms related to labor issues. The purpose of this study is to determine the factors that influence employment in East Java Province in 2010-2017. The variables used in this study are employment, wages, population and Gross Regional Domestic Product (GRDP). The data used in this study is panel data. The analysis tool used is panel data regression analysis. The results in this study using the model fixed effect are the variables of labor, wages, population and Gross Regional Domestic Product (GRDP) affecting employment in East Java. The policy recommendations carried out are programs to improve the quality and productivity of the workforce, programs for expanding and placing workers, developing industrial relations and sharia work programs and labor inspection and labor protection programs.